Pembuatan Kamus Bahasa sebagai Sarana Pelestarian Bahasa Dayak Pitap - Ludina, Kurnia; An’amta, Dimas Asto Aji; Rian; Anwar, Muhammad Andika; Salsabila, Nabila; Sabila, Sahla Ghina; Ulfa, Ryusda; Yolianda, Chintia; Mutia; Irfan, Muhammad (Prodi Sosiologi FISIP ULM, 2025)
This community service project was carried out in Langkap Village, Tebing Tinggi District, Balangan Regency, South Kalimantan, for 57 days, from July 17 to September 11, 2025. The main issue faced by the community was the decreasing ability of the younger generation to understand the equivalence of the Dayak Pitap language in Indonesian. Although the language is still used in daily life, many words have begun to lose their meaning and understanding among younger speakers. In response to this situation, the project focused on developing a Dayak Pitap–Indonesian Dictionary as a concrete effort to preserve the local language and provide an accessible learning resource for the community. The implementation used a participatory approach through live-in, field observation, and in-depth interviews with traditional leaders, including the Head of Adat, Deputy Head of Adat, and the Balian of Kaitan Customary Hall. The program began with the socialization of activities, followed by vocabulary collection, translation, validation, transcription, alphabetical arrangement, and book design. The result was a total of 396 validated vocabulary entries from 717 words collected. The final product, available in both printed and digital (PDF) forms, serves as a learning medium and documentation tool for the Dayak Pitap language. The existence of this dictionary is expected to increase awareness among the younger generation about the importance of preserving their mother tongue as part of the Dayak Pitap cultural identity. This project marks an initial yet meaningful step toward maintaining the local linguistic heritage for future generations.